Leadless left ventricular endocardial pacing in nonresponders to conventional cardiac resynchronization therapy. Issue 9 (9th May 2020) - Sidhu, Baldeep S.; Porter, Bradley; Gould, Justin; Sieniewicz, Benjamin; Elliott, Mark; Mehta, Vishal; Delnoy, Peter P. H. M.; Deharo, Jean‐Claude; Butter, Christian; Seifert, Martin; Boersma, Lucas V. A.; Riahi, Sam; et al.
Abstract: Background: Endocardial pacing may be beneficial in patients who fail to improve following conventional epicardial cardiac resynchronization therapy (CRT). The potential to pace anywhere inside the left ventricle thus avoiding myocardial scar and targeting the latest activating segments may be particularly important. The WiSE‐CRT system (EBR systems, Sunnyvale, CA) reliably produces wireless, endocardial left ventricular (LV) pacing. The purpose of this analysis was to determine whether this system improved symptoms or led to LV remodeling in patients who were nonresponders to conventional CRT. Method: An international, multicenter registry of patients who were nonresponders to conventional CRT and underwent implantation with the WiSE‐CRT system was collected. Results: Twenty‐two patients were included; 20 patients underwent successful implantation with confirmation of endocardial biventricular pacing and in 2 patients, there was a failure of electrode capture. Eighteen patients proceeded to 6‐month follow‐up; endocardial pacing resulted in a significant reduction in QRS duration compared with intrinsic QRS duration (26.6 ± 24.4 ms; P =  .002) and improvement in left ventricular ejection fraction (LVEF) (4.7 ± 7.9%; P  = .021). The mean reduction in left ventricular end‐diastolic volume was 8.3 ± 42.3 cm 3 ( P =  .458) and left ventricular end‐systolic volume (LVESV) was 13.1 ± 44.3 cm 3 ( P =  .271), which were statistically nonsignificant. Overall, 55.6% of patients had improvement in their clinical composite score and 66.7% had a reduction in LVESV ≥15% and/or absolute improvement in LVEF ≥5%. Conclusion: Nonresponders to conventional CRT have few remaining treatment options. We have shown in this high‐risk patient group that the WiSE‐CRT system results in improvement in their clinical composite scores and leads to LV remodeling.